Ibn Khaldun: his contribution to the science of civilisation - Akhmetova, Elmira (IAIS, 2014)
ÑAbd al-RaÍmÉn Ibn KhaldËn was a Muslim historiographer and historian of Arab origin, and one of the founding “fathers” of modern historiography, sociology and economics. He is best known to modern readers for his Muqaddimah (Prolegomena [To History]), the introductory book to the magnificent seven-volume account on history of the world entitled KitÉb al-ÑIbar (Book of History), which outlined the basic foundations of the science of civilisation. This work was designated by the well-known British historian, Arnold J. Toynbee, as a “philosophy of history which is undoubtedly the greatest work of its kind that has ever yet been created by any mind in any time or place.” Another British scholar, Robert Flint, commented on the significance of Ibn KhaldËn accordingly: “as a theorist of history he had no equal in any age or country until Vico appeared, more than three hundred years later. Plato, Aristotle, and Augustine were not his peers, and all others were unworthy of being even mentioned along with him.”